A Study Of Three Test Sites Comparing Theoretical Ultimate Pile Capacities, Static Pile Load Tests, And Psuedo Static Pile Load Test Results - Richard D. Short (Deep Foundations Institute, 2000)
The Pseudo Static Pile Load Test, PLT, is a rapid method for determining pile capacity. Pile design is usually based on theoretical calculations of ultimate load capacity using soil data from a field investigation. The pile capacity is confirmed during construction by analysis of blow counts using dynamic formulae, dynamic pile monitoring, and load testing. Load testing is the most direct and reliable method of determining the actual capacity of a pile. Conventional load testing procedures, however, are time consuming and expensive. A typical load test requires installation of two to four reaction piles, construction of a high-capacity steel test frame, hydraulic jacks, and dial gauges, and will typically take one to three days per pile. Costs for load tests range from $10,000 to $20,000 per test. The Pile Load Test machine features a 25-tonne weight mounted on a mobile test frame. PLT load tests can be performed in a matter of minutes once the equipment has been mobilized to the site. This paper examines three test sites where the PLT test method was used and compares the results to conventional load test results and theoretical capacity calculations.